Displacement and debt – the role of debt in returning to work after displacement. Issue 5 (8th April 2021) - Bednarzik, Robert; Kern, Andreas; Hisnanick, John
Abstract : Purpose: This paper aims to analyze the question of how household indebtedness impacts households' incentives to search for and accept work after displacement. Design/methodology/approach: To analyze the relationship between household indebtedness and unemployment duration, this paper applies standard proportional hazard models. For data, this paper relies on the longitudinal US National Survey of Income and Program Participation (SIPP), covering the period between 2008 and 2012. Findings: The findings show that a 10% increase in household debt increases the likelihood (hazard) of leaving unemployment by 0.2%–0.4% points. Independent of measuring a household's indebtedness and in light of a series of robustness tests, the results indicate that the pressure of servicing an existing debt burden forces individuals to return to work. Social implications: From a policy perspective, the research findings support the notion that household indebtedness plays an important mediating role for labor market outcomes through influencing households' incentives to return to work after displacement. This finding has important implications for the design of effective policy responses to mass layoffs during the current pandemic. Originality/value: A key innovation of the research is that we can show that household indebtedness impacts the labor supply side. From a macroeconomic perspective, this insight is important in better understanding the role of increased indebtedness (and financialization) in amplifying aggregate macroeconomic dynamics.